Ocular manifestations of recent viral pandemics: A literature review - Taha, Mohammad J. J.; Abuawwad, Mohammad T.; Alrubasy, Warda A.; Sameer, Shams Khalid; Alsafi, Taleb; Al-Bustanji, Yaqeen; Abu-Ismail, Luai; Nashwan, Abdulqadir J. (Frontiers in Medicine, 2022)
Viral pandemics often take the world by storm, urging the medical community to prioritize the most evident systemic manifestations, often causing ocular manifestations to go unnoticed. This literature review highlights the ocular complications of the Monkeypox, SARS-CoV-2, MERS, Ebola, H1N1, and Zika viruses as the most recent viral pandemics. Research into the effects of these pandemics began immediately. Moreover, it also discusses the ocular complications of the vaccines and treatments that were used in the scope of the viral pandemics. Additionally, this review discusses the role of the eye as an important route of viral transmission, and thereafter, the International recommendations to reduce the incidence of viral transmission were mentioned. Lastly, this paper wants to lay out a platform for researchers who want to learn more about how viruses show up in the eye.